Seismic Fragility of Ordinary Reinforced Concrete Shear Walls with Coupling Beams Designed Using a Performance-Based Procedure - Seong-Ha Jeon; Ji-Hun Park (Applied Sciences, 2020)
The seismic performance of ordinary reinforced concrete shear walls, that are commonly used in high-rise residential buildings in Korea (h < 60 m), but are prohibited for tall buildings (h ≥ 60 m), is evaluated in this research project within the framework of collapse probability. Three bidimensional analytical models comprised of both coupled and uncoupled shear walls exceeding 60 m in height were designed using nonlinear dynamic analysis in accordance with Korean performance-based seismic design guidelines. Seismic design based on nonlinear dynamic analysis was performed using different shear force amplification factors in order to determine an appropriate factor. Then, an incremental dynamic analysis was performed to evaluate collapse fragility in accordance with the (Federal Emergency Management Agency) FEMA P695 procedure. Four engineering demand parameters including inter-story drift, plastic hinge rotation angle, concrete compressive strain and shear force were introduced to investigate the collapse probability of the designed analytical models. For all analytical models, flexural failure was the primary failure mode but shear force amplification factors played an important role in order to meet the requirement on collapse probability. High-rise ordinary reinforced concrete shear walls designed using seven pairs of ground motion components and a shear force amplification factor ≥ 1.2 were adequate to satisfy the criteria on collapse probability and the collapse margin ratio prescribed in FEMA P695.